The Implementation of iSpring Quiz Maker as The Online Exam Tool of Physics Worklab during the Covid-19 Pandemic - Samuel Gideon; Anna Angela Sitinjak; Herry Darmadi; Muhammad Rafli (Program Studi Pendidikan Fisika, UIN Raden Fatah Palembang, 2021)
One of the implementation of advances in information and communication technology that can be used for online exam is the iSpring Quiz Maker. This research aims to: (1) determine the feasibility of iSpring Quiz Maker as the online exam tool of physics worklab; (2) determine the student interest responses in using iSpring Quiz Maker as the online exam tool of physics worklab; as well as (3) determine the effectiveness of iSpring Quiz Maker as the online exam tool of physics worklab. The method of this research is research and development (R & D) by applying the ADDIE (analysis stage, design stage, development stage, implementation stage and evaluation stage) model. The results showed that: (1) iSpring Quiz Maker is very feasible as physics worklab online exam tool based on the assessment of both material and media expert validators; (2) Students are very interested in using iSpring Quiz Maker as physics worklab online exam tool; and (3) iSpring Quiz Maker has not been effective as physics worklab online exam tool because the percentage of the total students who got score of 50 is 77.6% while the percentage of the total students who got score > 50 is 22.4%.